Effect of melatonin on oxidative status of rat brain, liver and kidney tissues under constant light exposure - Baydas, G; Erçel, E; Canatan, H; Dönder, E; Akyol, A (John Wiley & Sons Ltd, 2001)
An enormous amount of data has been published in recent years demonstrating melatonin's defensive role against toxic free radicals. In the present study, we examined the role of melatonin as an antioxidant against the effect of continuous light exposure. Rats were divided into three groups. Control rats (group A) were kept under natural conditions whereas other group of rats (group B and C) were exposed to constant light for inhibition of melatonin secretion by the pineal gland. Group C rats also received melatonin via s.c. injection (1 mg kg(-1) body weight day(-1)). At the end of experiment, ail animals were sacrificied by decapitation, serum and tissue samples were removed for determination of malondialdehyde (MDA), a product of lipid peroxidation, conjugated dienes levels and glutathione peroxidase (GSH-Px) activity levels. It was found that lipid peroxidation was increased in the rats which were exposed to constant light. Melatonin injection caused a decrease in lipid peroxidation, especially in the brain. In addition, melatonin application resulted in increased GSH-Px activity, which has an antioxidant effect. Thus, melatonin is not only a direct scavenger of toxic radicals, but also stimulates the antioxidative enzyme GSH-Px activity to detoxify hydroxyl radical produced by constant light exposure. Copyright (C) 2001 John Wiley & Sons, Ltd.
Keywords: GSH-Px; light exposure; lipid peroxidation; melatonin